2004
DOI: 10.1021/ac034138m
|View full text |Cite
|
Sign up to set email alerts
|

Mass Analysis of Water-Soluble Polymers by Mobility Measurement of Charge-Reduced Ions Generated by Electrosprays

Abstract: Aqueous solutions of poly(ethylene glycol) (PEG) in a 10 mM ammonium acetate buffer are electrosprayed, and the maximum charge state on the resulting gas-phase ions is reduced to unity using a radioactive source. The mobility distribution of these charged particles is then measured in air in a differential mobility analyzer of unusually high resolution. The relation Z(m) between the mobility Z of a polymer molecule and its mass m is determined by means of narrowly distributed PEG mass standards. The molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 37 publications
1
72
0
Order By: Relevance
“…This upper limit exceeds that inferred from the slope of Figure 5 by just 6.4%, confirming the notion that the clusters are fairly compact. Similar studies [24] with singly charged polyethylene glycol (PEG) clusters in the mass range from 4000 to 700,000 have reported a cluster density of 1.23 g/cc, in fair agreement with the known density of PEGs with masses above a few thousand ( PEG ϭ 1.21 g/cc [24]), apparently confirming the near spherical shape of these clusters. This study, however, did not measure ion mass directly, while a subsequent DMA-MS investigation has inferred the smaller value PEG ϭ 1.055 g/cc [25].…”
Section: Relation Between Mobility Mass and Cluster Diametersupporting
confidence: 69%
“…This upper limit exceeds that inferred from the slope of Figure 5 by just 6.4%, confirming the notion that the clusters are fairly compact. Similar studies [24] with singly charged polyethylene glycol (PEG) clusters in the mass range from 4000 to 700,000 have reported a cluster density of 1.23 g/cc, in fair agreement with the known density of PEGs with masses above a few thousand ( PEG ϭ 1.21 g/cc [24]), apparently confirming the near spherical shape of these clusters. This study, however, did not measure ion mass directly, while a subsequent DMA-MS investigation has inferred the smaller value PEG ϭ 1.055 g/cc [25].…”
Section: Relation Between Mobility Mass and Cluster Diametersupporting
confidence: 69%
“…Polyethylene glycols (PEGs) in the size range of 4k to 700 kDa were used to establish that molecular weight and mobility diameter could be correlated by a one-third power law [47] a correlation that had already been established for proteins three years prior [11]. Similar behavior has been reported for water insoluble polymers [48].…”
Section: 2polymers and Proteinsmentioning
confidence: 64%
“…Using uncertainty analysis, it can be shown that a 15% variation in mobility diameter results in a 45% variation in density which partially explains this wide scatter of densities in the literature and strengthens the above hypothesis. The same rationale may also explain the scatter of densities found in PEGs [47,51]. Curiously, the lower density in all cases have been reported only with TSI Inc designed DMAs and this perhaps is because of inaccurate or imprecise DMA geometry designed and manufactured by them.…”
Section: 2polymers and Proteinsmentioning
confidence: 91%
See 1 more Smart Citation
“…The size range of 10 to 200 nm is therefore of great interest, and covered by the so-called nano-differential mobility analysis (nano DMA) [8]. Combined with a modified nano electrospray source (nES) for nanoaerosol generation, and bipolar charging process to deliver mostly singly charged ions [9,10], it has been demonstrated that the analysis of intact biospecific protein complexes [11,12], viruses [11], virus antibody [13], virus receptor [13], bacterio phages [14], and polymers [15,16] is possible, and delivers a lot of new knowledge.…”
mentioning
confidence: 99%